ANALISIS PERBANDINGAN USAHATANI KELAPA SAWIT POLA SWADAYA LAHAN MINERAL DAN LAHAN GAMBUT DI KOTA DUMAI - Rahayu, Nindy Juli; Hadi, Syaiful; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Palm oil is a plantation that has contributes to increasing economic growth in Riau. Oil palm plantation open up employment opportunities for the community and provide benefit for oil palm farmers. Dumai city in each year shows an increase in area, namely in 2013 amounting to 36.345.00 ha and in 2017 covering an area of 38.079,00 ha. Land is the main factor in oil palm cultivation in order to produce high FFB (Fresh Fruit Benefit), limitied land causes farmers to switch to oil palm cultivation from mineral land to marginal land, one of them is peat land, this is shown in Dumai city peat land is in the 7th rank out of 9 Regencies the city reaches 159.596 ha. This reset is there difference in productivity between mineral land and peat land as well as income between mineral land peat land in Dumai city. This study was conducted in Dumai city with purposive sampling technique where the criteria of oil palm farmers were self-help patterns, on mineral land and peat land with productive age of adolescents in the category of 9-13 years, and to compare them using test analysis of independent sample statistic. This reset shows that the yield of FFB (Fres Fruit Benefit) productivity of oil palm farmers on mineral land amounted to 13.151 tons higher than that of peat land which is 6.766 tons. As well as net income in mineral land of Rp19.367,894,97 land area/year is higher compared to peat land of Rp3.573.741,28 land area/year. Keywords: palm oil, productivity, income, mineral land, peat land.